Strategic differentiation and integration of genomic-level heritabilities facilitate individual differences in preparedness and plasticity of human life history - Woodley of Menie, Michael A.; Figueredo, Aurelio José; Cabeza de Baca, Tomás; Fernandes, Heitor B. F.; Madison, Guy; Wolf, Pedro S. A.; Black, Candace J. (Frontiers in Psychology, 2015)
Life history (LH) strategies refer to the pattern of allocations of bioenergetic and material resources into different domains of fitness. While LH is known to have moderate to high population-level heritability in humans, both at the level of the high-order factor (Super-K) and the lower-order factors (K, Covitality, and the General Factor of Personality), several important questions remain unexplored. Here, we apply the Continuous Parameter Estimation Model to measure individual genomic-level heritabilities (termed transmissibilities). These transmissibility values were computed for the latent hierarchical structure and developmental dynamics of LH strategy, and demonstrate; (1) moderate to high heritability of factor loadings of Super-K on its lower-order factors, evidencing biological preparedness, genetic accommodation, and the gene-culture coevolution of biased epigenetic rules of development; (2) moderate to high heritability of the magnitudes of the effect of the higher-order factors upon their loadings on their constituent factors, evidencing genetic constraints upon phenotypic plasticity; and (3) that heritability of the LH factors, their factor loadings, and the magnitudes of the correlations among factors, are weaker among individuals with slower LH speeds. The results were obtained from an American sample of 316 monozygotic (MZ) and 274 dizygotic (DZ) twin dyads and a Swedish sample of 863 MZ and 475 DZ twin dyads, and indicate that inter-individual variation in transmissibility is a function of individual socioecological selection pressures. Our novel technique, opens new avenues for analyzing complex interactions among heritable traits inaccessible to standard structural equation methods.